2008
DOI: 10.1186/cc7009
|View full text |Cite
|
Sign up to set email alerts
|

Partial pressure of end-tidal carbon dioxide successful predicts cardiopulmonary resuscitation in the field: a prospective observational study

Abstract: Introduction Prognosis in patients suffering out-of-hospital cardiac arrest is poor. Higher survival rates have been observed only in patients with ventricular fibrillation who were fortunate enough to have basic and advanced life support initiated soon after cardiac arrest. An ability to predict cardiac arrest outcomes would be useful for resuscitation. Changes in expired end-tidal carbon dioxide levels during cardiopulmonary resuscitation (CPR) may be a useful, noninvasive predictor of successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(106 citation statements)
references
References 33 publications
4
82
2
2
Order By: Relevance
“…Studies have confirmed that the measurement of ETCO 2 is predictive of the outcomes of CPR. 56,60 Human studies have suggested that ETCO 2 correlates closely with successful resuscitation and predicts the outcome of CA reliably 61,62 The initial ETCO 2 immediately after unclamping the ETT did not correlate with ROSC in the present study. This has already been described in previous animal studies.…”
Section: Discussioncontrasting
confidence: 51%
“…Studies have confirmed that the measurement of ETCO 2 is predictive of the outcomes of CPR. 56,60 Human studies have suggested that ETCO 2 correlates closely with successful resuscitation and predicts the outcome of CA reliably 61,62 The initial ETCO 2 immediately after unclamping the ETT did not correlate with ROSC in the present study. This has already been described in previous animal studies.…”
Section: Discussioncontrasting
confidence: 51%
“…Eleven studies showed that physiological monitoring values (ETCO 2 , coronary perfusion pressure, venous oxygen saturation) increased when ROSC was achieved (LOE 4) [171][172][173][174][175][176][177][178]135,179,180 and that they may be an indication of ROSC before it can be seen in vital signs. 181 Five of the studies found that ETCO 2 was accurate for predicting patients who could not be resuscitated; some gave a time frame for that prediction of 20 minutes (LOE 4).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…181 Five of the studies found that ETCO 2 was accurate for predicting patients who could not be resuscitated; some gave a time frame for that prediction of 20 minutes (LOE 4). 136,174,178,182,183 However, 2 studies documented patients who did not meet the ETCO 2 range but who survived (LOE 4). 174,184 Multiple studies by 1 group (LOE 4) [175][176][177] showed that when ETCO 2 exceeded 10 mm Hg, all patients achieved ROSC.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…For this reason, capnography is now recommended in cardiopulmonary resuscitation to detect the return of spontaneous circulation by identifying resuming pulmonary perfusion. 30 Our study has some important limitations. Respiratory therapists actively involved in caring for children rather than research staff recorded the data.…”
Section: Discussionmentioning
confidence: 90%